A passenger rail truck design methodology. (5th August 2014) - Horak, D.; Wormley, D.N.
A design methodology is developed for passenger vehicle rail trucks in which primary and secondary suspension parameters and wheel/rail parameters are determined to meet a set of dynamic performance indices. The methodology partitions the design task into two basic tradeoff studies: (1) a stability–curving tradeoff and (2) a lateral ride quality–secondary stroke tradeoff. The design methodology is illustrated with both high–speed intercity and lower–speed urban rail truck designs.